2019
DOI: 10.14716/ijtech.v10i5.2297
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Dynamic Axial Crushing on a Square Tube with Eight Holes Used as a Crush Initiator

Abstract: Thin-walled square steel tubes are part of automobile structures, used as impact energy absorbers on crush boxes. Under axial crushing, such tubes sometimes produces unpredictable folding forms. There are three modes of dynamic axial crushing folding forms: the symmetric collapse mode; the asymmetric mixed collapse mode A; and the asymmetric mixed collapse mode B. The objective of this paper is to develop a theoretical prediction for the three modes on a thin-walled square steel tube with eight holes used as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The existence of a hole will influence the amount of absorption energy in mode I, where the effect of a round hole on a square tube has been calculated [18,19]. While here it is studied for the influence of elliptical holes on 2 opposite sides which affect the horizontal hinge line, with the following calculations: From Fig.…”
Section: Energy Calculation Of the Horizontal Hinge Line On A Square ...mentioning
confidence: 99%
“…The existence of a hole will influence the amount of absorption energy in mode I, where the effect of a round hole on a square tube has been calculated [18,19]. While here it is studied for the influence of elliptical holes on 2 opposite sides which affect the horizontal hinge line, with the following calculations: From Fig.…”
Section: Energy Calculation Of the Horizontal Hinge Line On A Square ...mentioning
confidence: 99%
“…Lightweight and large energy absorption capacity are currently the main design priorities in the automobile and aerospace sectors to minimize the amount of material and hence fuel consumption (Helou & Kara, 2017;Ye et al, 2020). Traditionally, the role of energy absorption has been filled by thin-walled tubes (Malawat et al, 2019). Recent findings indicated that polylactic acid (PLA) lattice structures might be used as sacrificial claddings as material and structure protection gear (Santos et al, 2021;Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subramaniyan et al (2014) found that the quantity of circular cut-outs contributed to decreasing the PF in circular and square tubes. Other studies examined the impact of crush initiator placement, such as drilling holes (Estrada et al, 2019) and multiple holes (Malawat et al, 2019;Dionisius et al, 2022) in square steel tubes, leading to improved crashworthiness performance. Researchers have examined the use of V-notch, groove (Balaji and Annamalai, 2017), and tapered (Asanjarani et al, 2018) shapes as effective crush initiators, reducing the initial force spikes without compromising the total energy absorption.…”
mentioning
confidence: 99%